Elimination of Escherichia coli in Water Using Cobalt Ferrite Nanoparticles: Laboratory and Pilot Plant Experiments - Gastelo, Elmer (2019)
E.G. would like to thank the Peruvian Council for Science and Technology (CONCYTEC) for the Scholarship. Roberto Jorge Candal is acknowledged for the SEM characterization of the samples.